Nursing Management of the Patient Undergoing Focused Ultrasound: A New Treatment Option for Essential Tremor. Issue 5 (October 2017) - Shaw, Katherine Dale; Johnston, Amy Sue; Rush-Evans, Shelly; Prather, Susan; Maynard, Kathy
Abstract : ABSTRACT: Essential tremor (ET) is among the most common neurological movement disorders that causes postural or action tremors, with an estimated prevalence nationwide of less than 3% of the population. The incidence of ET increases with age but often affects younger adults and has a familial trait association. Depending on disease progression, ET can cause significant limitations for individuals, in many cases, significantly limiting their ability to perform activities of daily living and occupational responsibilities. Until recently, treatment of ET heavily relied on medication management and invasive surgery, such as deep brain stimulation. With advances in the use of focused ultrasound (FUS) for treatment of various medical conditions, recent clinical trials have revealed positive outcomes with the use of FUS as a less invasive approach to treat patients with medication-refractory ET. In a large academic medical center in the mid-Atlantic region, the Department of Neurosurgery conducted a continued access study, recently approved by the Food and Drug Administration, to evaluate the effectiveness of transcranial FUS thalamotomy for the treatment of medication-refractory ET. One patient's experience will be introduced, including discussion of evidence-based treatment options for ET and information on the nursing management of the patient undergoing FUS thalamotomy.